Evidence of non‐stationary relationships between climate and forest responses: Increased sensitivity to climate change in Iberian forests. (3rd July 2020) - Astigarraga, Julen; Andivia, Enrique; Zavala, Miguel A.; Gazol, Antonio; Cruz‐Alonso, Verónica; Vicente‐Serrano, Sergio M.; Ruiz‐Benito, Paloma
Abstract: Climate and forest structure are considered major drivers of forest demography and productivity. However, recent evidence suggests that the relationships between climate and tree growth are generally non‐stationary (i.e. non‐time stable), and it remains uncertain whether the relationships between climate, forest structure, demography and productivity are stationary or are being altered by recent climatic and structural changes. Here we analysed three surveys from the Spanish Forest Inventory covering c . 30 years of information and we applied mixed and structural equation models to assess temporal trends in forest structure (stand density, basal area, tree size and tree size inequality), forest demography (ingrowth, growth and mortality) and above‐ground forest productivity. We also quantified whether the interactive effects of climate and forest structure on forest demography and above‐ground forest productivity were stationary over two consecutive time periods. Since the 1980s, density, basal area and tree size increased in Iberian forests, and tree size inequality decreased. In addition, we observed reductions in ingrowth and growth, and increases in mortality. Initial forest structure and water availability mainly modulated the temporal trends in forest structure and demography. The magnitude and direction of the interactive effects of climate and forest structure on forest demography changed over the two time periods analysed indicating non‐stationary relationships between climate, forest structure and demography. Above‐ground forest productivity increased due to a positive balance between ingrowth, growth and mortality. Despite increasing productivity over time, we observed an aggravation of the negative effects of climate change and increased competition on forest demography, reducing ingrowth and growth, and increasing mortality. Interestingly, our results suggest that the negative effects of climate change on forest demography could be ameliorated through forest management, which has profound implications for forest adaptation to climate change. Abstract : Based on the theoretical framework, climate change direct and indirect effects (i.e. modulated by forest structure) on forest demography changed over two consecutive time periods (i.e. periods 1 and 2) indicating non‐time stable relationships. Above‐ground productivity increased due to a positive balance between ingrowth, growth and mortality. The negative effects of climate change and increased competition on forest demography increased over time. In most cases the direct and indirect effects of climate change on forest demography had opposite directions suggesting that changes in forest structure could be used to ameliorate the negative climate change effects on forest demography.